A Performance Analysis of a Stand-Up Paddle Board Marathon Race. Issue 6 (June 2017) - Schram, Ben L.; Hing, Wayne A.; Climstein, Mike; Furness, James W.
Abstract : Abstract: Schram, BL, Hing, WA, Climstein, M, and Furness, JW. A performance analysis of a stand-up paddle board marathon race. J Strength Cond Res 31(6): 1552–1556, 2017—Stand-up paddle boarding (SUP) is a rapidly growing sport and recreational activity in which little scientific research exists. A review of the literature failed to identify a single article pertaining to the physiological demands of SUP competition. The purpose of this study was to conduct a performance analysis of a national-level SUP marathon race. Ten elite SUP athletes (6 male and 4 female athletes) were recruited from the Stand Up Paddle Surfing Association of Australia to have their race performance in the Australian Titles analyzed. Performance variables included SUP speed, course taken, and heart rate (HR), measured with a 15-Hz global positioning system unit. Results demonstrated that there was a variation in distance covered (13.3–13.9 km), peak speed (18.8–26.4 km·h −1 ), and only moderate correlations ( r = 0.38) of race result to distance covered. Significantly greater amounts of time were spent in the 5- to 10-km·h −1 speed zones ( p ⩽ 0.05) during the race. Peak HR varied from 168 to 208 b·min −1 among the competitors with the average HR being 168.6 ± 9.8 b·min −1 . Significantly higher durations were spent in elevated HR zones ( p ⩽ 0.05) with participants spending 89.3% of their race within 80–100% of their age-predicted HRmax. Marathon SUP races seem to involve a high aerobic demand, with maintenance of near-maximal HRs required for the duration of the race. There is a high influence of tactical decisions and extrinsic variables to race results. These results provide a greater understanding of the physiological demands of distance events and may assist in the development of specialized training programs for SUP athletes.